Informal Indonesian and the Spirit of Pluralis - Soepomo Poedjosudarmo (Universitas Sanata Dharma, 2014)
This brief paper deals with the emergence of the informal style of Indonesian, especially from the point of view of its motive, its function, its form and the effect of the vitality of the local vernaculars. It is the result of long observation and participation as a citizen of Indonesia, who speaks Javanese as a native speaker and who has spoken Indonesian from the time of its inception Keywords: diglossic, informal Indonesian, code-switchin